2007
DOI: 10.1016/j.canlet.2006.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum angiocidin levels in hepatocellular carcinoma

Abstract: Angiocidin, a tumor-secreted protein, was measured in serum of 27 healthy volunteers and 33 hepatocellular carcinoma (HCC) patients. Healthy controls either hepatitis B surface antigen (HBsAg) positive or negative showed undetectable levels. Patients had levels of angiocidin ranging from 15.09-195.73 pg/ml. Patients with stages III-IV had higher levels of angiocidin (97±13 pg/ml, n=17) compared to those with stages I-II (63±37 pg/ml, n=16), p<0.043. Patients with microsatellite tumor nodules had higher average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…During their differentiation, the cells became flattened, elongated and firmly attached to the tissue culture plastic. Earlier reports have indicated the presence of angiocidin in tumor-conditioned medium and in the serum of cancer patients (Sabherwal et al, 2007). Because of the high sequence similarity between angiocidin and S5a, we postulated that these proteins could share a similar function, inducing THP-1 adhesion and/or differentiation.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…During their differentiation, the cells became flattened, elongated and firmly attached to the tissue culture plastic. Earlier reports have indicated the presence of angiocidin in tumor-conditioned medium and in the serum of cancer patients (Sabherwal et al, 2007). Because of the high sequence similarity between angiocidin and S5a, we postulated that these proteins could share a similar function, inducing THP-1 adhesion and/or differentiation.…”
Section: Resultsmentioning
confidence: 82%
“…Recent studies have reported that S5a/angiocidin inhibits endothelial cell proliferation and induces endothelial cell apoptosis and antitumor activities that are related to the activity of polyubiquitin conjugates (Saeki and Tanaka, 2008). Restructuring angiocidin offers a variety of mechanisms for antitumor activity in vitro and in vivo (Sabherwal et al, 2007;L'Heureux et al, 2010;Liebig et al, 2009;Kremlev et al, 2008;Yang et al, 2006). In this study, we focused on another aspect of the antitumor activity of S5a, by inducing the differentiation of THP-1 cells into macrophages.…”
Section: Endogenous S5a Is a Crucial Protein For Monocyte Self-regulamentioning
confidence: 99%
See 1 more Smart Citation
“…Colon cancer cells expressing low-level angiocidin exhibited very low proliferation rates than high expression cells. In vivo, nude mice injected with low angiocidin expression colon cancer cells develop significantly smaller tumors than the mice injected with normal cells [8][9][10][11][12] . These above results suggest that angiocidin may play a key role in tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Overexpression of angiocidin has been shown in many solid epithelial tumors, and increased levels of angiocidin have been demonstrated in the serum of patients with different epithelial malignancies. 10,11 Preliminary reports have shown low to negligible expression of angiocidin in normal adult tissues, making it an attractive molecular target for tumor-specific therapy. 9,12,13 The protumor effects of angiocidin are the result of highaffinity binding interactions with extracellular matrix proteins including thrombospondin-1 (TSP-1), a matrix protein produced in tumors by activated stromal cells of mesenchymal origin.…”
mentioning
confidence: 99%